Minimally Invasive Lateral Transpsoas Interbody Fusion at the L4/5 Level: A Review of 61 Consecutive Cases. Issue 4 (22nd February 2018) - Januszewski, Jacob; Vivas, Andrew C; Bach, Konrad; Gandhi, Shashank V; Paluzzi, Jason, Juan S Uribe
Abstract: BACKGROUND: Reported complication rates for minimally invasive lateral transpsoas interbody fusion (MIS-LIF) vary widely. The risk of lumbar plexus injury is particularly concerning at the L4-5 disc space. We report our experience with MIS-LIF at L4-5, and discuss the risk profile of transpsoas approaches at this level. OBJECTIVE: To evaluate safety of MIS-LIF at the L4/5 level. METHODS: This was a retrospective, IRB-approved cohort study performed at a single institution from 2011 to 2016. Patients who underwent MIS-LIF at L4-5 were included. Patients with multilevel fusions were excluded. We analyzed postoperative sensory and motor deficits, the date of resolution, health-related quality-of-life scores, and rate of fusion. RESULTS: Over a 5-yr period, 303 patients underwent MIS-LIF at our institution. Sixty-one patients had surgery only at the L4-5 level (20.1%). Twelve of these patients (19.6%) had postoperative neurological deficits including 2 motor deficits (2/61 = 3.2%) and 11/61 (18%) sensory deficits. At 12-mo follow-up, 3 of the deficits persisted for a long-term complication rate of 3/61 (4.9%), motor complication 2/61 (3.2%). Hospital stay and follow-up averaged 2.1 d and 15 mo. Average Oswestry Disability Index improved from 51.1 to 31.1 ( P  < .00001). Visual Analog Scale (VAS) improved from 7.4 to 3.9 ( P  < .016). There were no reoperations secondary to hardware failure or pseudoarthrosis. Fusion rate was 89% at 12 mo. CONCLUSION: MIS-LIF is a safe and effective approach for interbody fusion at L4-5 with low rate of lumbar plexus injury. Most immediate postoperative deficits will resolve over time.